Leadership 3.0 Based Principalâs Leadership to Improve Teachersâ Work in Multicultural Society - Gunarhadi, Tukiyo, Joko Nurkamto, Siswandari & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This study aims at describing whether leadership 3.0 based principalâs leadership canimprove teachersâ work in multicultural society. To answer the problem, the writer didliterary study and resuming relevant researches. Leadership implemented by a principalin an education institution (school) influences the teachersâ work. A good principalleadership is able to make the teachers do their assignment and obligation well. A goodpractice done by a principal will be an example of all members of the institution. Tomeet the hope, the writer did a study on leadership 3.0 based principalâs leadershipcovering six aspects, namely physicallity, intellectuality, emotionality, sociability,personability, and moral ability. Based on the study, it was concluded that leadership3.0 based principalâs leadership can improve teachersâ work in multicultural society.Keywords: leadership 3.0 based principalâs leadership, teachers work, multicultural society